A Dynamic Strain-Rate-Dependent Contact Model and Its Application in Hongshiyan Landslide. (29th May 2021) - Shi, Chong; Li, Wangyang; Meng, Qingxiang
Abstract : An earthquake-induced landslide, mainly affected by seismic movement, is a frequent large-scale geological hazard in hydraulic engineering. This paper proposed a rate-dependent strain-softened micromechanical contact model and implemented it in discrete element method code, namely, PFC. Using the PFC-FLAC coupling scheme, the Hongshiyan earthquake landslide is analyzed as a case study. The influence of the strain rate, damping, and topographic effect is discussed. The results indicate that the rate-dependent micromechanical model can give a reasonable seismic-induced failure process compared with the in situ situation and provide a numerical technique for earthquake-induced landslide analysis and rockfall hazard prediction.